MENINGKATKAN PEMBELAJARAN BERPIDATO DENGAN METODE PEMODELAN DI KELAS IX-A MTS MIFTAHUL ULUM KANIGORO KECAMATAN PAGELARAN KABUPATEN MALANG - Muhammad Husni (JURNAL PUSAKA, 2014)
One form of conversational skills are addressed. In this study, using the method of modeling speech learning. The goal of improving the process and learning outcomes addressed by the modeling method. This research method is class action research that shaped the implementation cycle, and each cycle carried out the plan, action, observation, and reflection. Data obtained from the action observation and interview, then analyzed to determine the advantages and disadvantages. Qualitatively, addressing the learning process increased, and quantitatively, addressing the learning outcomes also increased.Key words: learning speech, modeling methods, mts